2007
DOI: 10.1002/pola.21978
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated copolymers and terpolymers based on vinylidene fluoride and bearing sulfonic acid side‐group

Abstract: The radical co‐ and terpolymerization of perfluoro(4‐methyl‐3,6‐dioxaoct‐7‐ene) sulfonyl fluoride (PFSVE) with 1,1‐difluoroethylene (or vinylidene fluoride, VDF or VF2), hexafluoropropene (HFP), chlorotrifluoroethylene (CTFE), and bromotrifluoroethylene (BrTFE) is presented. Although PFSVE could not homopolymerize under radical initiation, it could be copolymerized in solution under a radical initiator with VDF, while its copolymerizations with HFP or CTFE led to oligomers in low yields. The terpolymerizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…We have found that r VDF = 1.20 ± 0.50 and r BDFE = 0.40 ± 0.15 at 75 °C showing that VDF is more reactive than BDFE and showing also that they are statistic copolymers as most of the copolymers of VDF 7. (a), 8 (c), 35–57 Compared with the reactivity ratios of other fluoromonomers able to copolymerize with VDF (Table 4), the value of the reactivity ratio of BDFE was found to be between that of HCFCF 2 (0.50) and that of F 2 CCF(CH 2 ) 3 SAc (0.41) (Table 4) but r VDF is much lower ( r VDF = 0.70 or 0.60, respectively vs. 1.20 in that present study). These values can be compared with the reactivity of other fluoromonomers able to copolymerize with VDF (Table 4),7 (a), 8 (c), 35–57 and with the values arising from the radical copolymerization of TFE with BDFE ( r TFE = 0.82; r BDFE = 0.24) 20…”
Section: Resultsmentioning
confidence: 83%
“…We have found that r VDF = 1.20 ± 0.50 and r BDFE = 0.40 ± 0.15 at 75 °C showing that VDF is more reactive than BDFE and showing also that they are statistic copolymers as most of the copolymers of VDF 7. (a), 8 (c), 35–57 Compared with the reactivity ratios of other fluoromonomers able to copolymerize with VDF (Table 4), the value of the reactivity ratio of BDFE was found to be between that of HCFCF 2 (0.50) and that of F 2 CCF(CH 2 ) 3 SAc (0.41) (Table 4) but r VDF is much lower ( r VDF = 0.70 or 0.60, respectively vs. 1.20 in that present study). These values can be compared with the reactivity of other fluoromonomers able to copolymerize with VDF (Table 4),7 (a), 8 (c), 35–57 and with the values arising from the radical copolymerization of TFE with BDFE ( r TFE = 0.82; r BDFE = 0.24) 20…”
Section: Resultsmentioning
confidence: 83%
“…In fact, starting from a VTEOS-feed molar percentage of 9.4 ( The hydrolysis of the sulfonyl fluoride group of these poly(VDFter-PFSVE-ter-VTEOS) terpolymers in a basic medium was studied to generate the sulfonic acid functions necessary for the proton conductivity. As the VDF groups are very sensitive to basic conditions, [34][35][36][37][38][39] the conversion of the -SO 2 F groups in the PFSVE units into -SO 3 Li in the terpolymer was achieved using Li 2 CO 3 (2 mol equivalents for 1 mol of SO 2 F group) at room temperature (Scheme 1).…”
Section: Synthesis Of Terpolymersmentioning
confidence: 99%
“…In this way, the vinyltriethoxysilane (VTEOS) units of the terpolymer help to bind and assemble the inorganic network into a continuous medium and the perfluoro(4-methyl-3,6-dioxaoct-7-ene) sulfonyl fluoride (PFSVE) chains are able to bridge the conduction paths in the hybrid membrane by way of their -SO 3 H-functionalized chain ends. The synthesis of such terpolymers was investigated through the radical terpolymerization of vinylidene fluoride (VDF), [30][31][32][33][34][35] PFSVE [36] and VTEOS (Scheme 1). To the best of our knowledge, no reports have been published as to the synthesis of such a type of copolymer or terpolymer, containing both Si(OR) 3 and SO 2 R 0 (R ¼ CH 3 , C 2 H 5 , etc.…”
mentioning
confidence: 99%
“…Recently, Dongyue Research Institute in China has developed a series of PFSI precursors, structurally similar to the ionomers reported by Sauguet et al In Scheme , the radical copolymerization of tetrafluoroethylene and perfluoro[2‐(2‐fluorosulfonylethoxy) propyl vinyl ether] the copolymerization was initiated using perfluoroacyl peroxide in fluorocarbon solvent. After conversion of –SO 2 F groups into –SO 3 Na or –SO 3 H, the PFSI membranes are proved to be a good alternative to Nafion ® in most applications.…”
Section: Introductionmentioning
confidence: 95%